Effect of concurrent geometry and roughness in interacting surfaces - Fosco, Cesar Daniel (2015)
We study the interaction energy between two surfaces, one of them flat, the other describable as the composition of a small-amplitude roughness and a slightly curved, smooth surface. The roughness, represented by a spatially random variable, involves Fourier wavelengths shorter than the (local) curvature radii of the smooth component of the surface. After averaging the interaction energy over the roughness distribution, we obtain an expression which only depends on the smooth component. We then approximate that functional by means of a derivative expansion, calculating explicitly the leading- and next-to-leading-order terms in that approximation scheme. We analyze the resulting interplay between shape and roughness corrections for some specific roughness models in the cases of electrostatic and Casimir interactions.